Performance analysis and enhancement of direct power control of DFIG based wind system - Mohamed Amine Beniss; Hassan El Moussaoui; Tijani Lamhamdi; Hassane El Markhi (Institute of Advanced Engineering and Science, 2021)
The paper proposes a complete modeling and control technique of variable speed wind turbine system (WTS) based on the doubly fed induction generator (DFIG). Two levels back-to-back converter is used to ensure the energy transfer between the DFIG rotor and the grid. The wind turbine to operate efficiently, a maximum power point tracking (MPPT) algorithm is implemented. Then, direct power control (DPC) strategy has been combined with the MPPT technique in order to guarantee the selection of the appropriate rotor voltage vectors and to minimize the active and reactive power errors. Finally, the simulation is performed by using MATLAB/simulink platform basing on 7.5KW DFIG wind generation system, and the results prove the effectiveness of our proposed control technique.